Profil Penderita Penyakit Tuberkulosis Paru yang Ditemukan di RSI PKU Muhammadiyah Pekajangan Pekalongan - Mardiani (E-Jurnal Kajen, 2025)
Tuberculosis is a disease caused by Mycobacterium tuberculosis. Tuberculosis usually attacks the lungs, which can then attack all parts of the body. This study aims to identify the profile of patients with Pulmonary Tuberculosis disease at RSI PKU Muhammadiyah Pekajangan Pekalongan based on age, gender, education, occupation, sputum laboratory images, X-ray images, BMI images, and treatment status. This type of research is descriptive research using a total sampling technique of as many as 431 patients. Data analysis using univariate analysis. The results showed that in terms of age, the most in pre-elderly (41-60 years) is 43%, the most gender in men is 56.6%, the most education in high school is 78.4%, the most work in private / honorarium is 34.8%, the most sputum lab picture in Mycobacterium TB detected and Rifampicin not resistance is 58.2%, the most X-ray picture in Primary TB is 60.1%, the picture of normal BMI is 91%, the most treatment status in Cured 6 months is 39.9%. The hospital need further improve health counseling for the community, especially for people with Pulmonary Tuberculosis.